FRI0361 INNATE VERSUSADAPTIVE IL-17A PRODUCING CELLS IN AXIAL SPONDYLOARTHRITIS. (June 2019) - rosine, nicolas; Koturan, Surya; Yahia, Hanane; Leloup, Claire; Bianchi, Elisabetta; Richard, Corinne Miceli; Rogge, Lars
Abstract : Background: IL-17A-inhibition has been very successful in AxSpA but the cell populations targeted by this new therapeutic remain unknown. This question is relevant because the recent failure of anti-IL-23 in AxSpA demonstrated that IL-23-independent IL-17-producing cells may be of particular relevance for SpA pathogenesis. Some data from literature suggests the involvement of MAIT, γδ T, and neutrophils as IL-17A producing cells in AxSpA (1–3). However, even though they may be responsible for IL-17A-mediated inflammation, it is still unclear which is the major IL-17A-producing cell population in this disease. Objectives: To assess and compare gene expression profiles of neutrophils, MAIT, γδ, CD4+ and CD8+ T cells from AxSpA patients. Methods: We recruited 5 healthy donors and 10 patients with a diagnosis of AxSpA according to the ASAS criteria. We compared the gene expression profiles of 5 sorted cell populations: 3 innate cell populations (neutrophils, MAIT and γδ T cells) and 2 adaptive cell populations (CD4+T and CD8+T) after cell stimulation by PMA + A23187 (calcium ionophore) + β1, 3 glucan (extracted from Aspergillus fumigatus hyphae). Published data suggested that neutrophils stimulation by Aspergillus fumigatus induces IL-17A production by these cells(4). For each of these cell populations, cytokine production and the expression of a panel of 755 genes (Autoimmune discovery panel from Nanostring including 43 genes for which a polymorphism was associated with AS) were assessed. Patient and control groups were compared with a Mann-Whitney test and comparison of cell populations was performed by a multigroup comparison. Results: There was no significant difference between patients and controls regarding gene expression profile of neutrophils, γδ T, CD4+T and CD8+T. We observed that 34 genes were differentially expressed between patients and controls in MAIT cells (p = 0.03, q = 0.1). In particular, T cell activation genes ( TBX21, AHR, ZAP70 ) and cell interaction genes ( ITAG6, CTNNB1, ICAM2, ITGB2, SELL ) were decreased in patients. Among AxSpA patients, MAIT cells were those significantly showing the highest level of IL-17A expression. IL23R and RORC were also more expressed by MAIT compared to others cell populations. IL-17A expression was very low in neutrophils but we observed that 18 out of the 43 AS associated genes were mainly expressed by neutrophils (p <0.05, q = 0.02), supporting the idea that they should be involved in the pathophysiology of the disease. Conclusion: These preliminary data confirm that the innate immune cells could play an important role in AxSpA. MAIT cells are at the forefront of the expression of IL-17A before γδ T, CD4+T and CD8+T. Neutrophils do not appear to participate in the production of IL-17A, but the high expression of AS linked genes in these cells suggests their involvement in AxSpA. References: [1] Appel H, et al. Analysis of IL-17(+) cells in facet joints of patients with spondyloarthritis suggests that the innate immune pathway might be of greater relevance than the Th17-mediated adaptive immune response. Arthritis Res Ther. 2011 [2] Kenna TJ, et al. Enrichment of circulating interleukin-17-secreting interleukin-23 receptor-positive γ/δ T cells in patients with active ankylosing spondylitis. Arthritis Rheum. 2012 [3] Gracey E, et al. IL-7 primes IL-17 in mucosal-associated invariant T (MAIT) cells, which contribute to the Th17-axis in ankylosing spondylitis. Ann Rheum Dis. 2016 [4] Taylor PR, et al. Activation of neutrophils by autocrine IL-17A-IL-17RC interactions during fungal infection is regulated by IL-6, IL-23, RORγt and dectin-2. Nat Immunol. 2014 Disclosure of Interests: nicolas rosine: None declared, Surya Koturan: None declared, Hanane Yahia: None declared, Claire Leloup: None declared, Elisabetta Bianchi: None declared, Corinne Miceli Richard Grant/research support from: MSD, Pfizer, AbbVie, Biogen, UCB, Novartis, Consultant for: Abbvie, Novartis, BMS, Lars Rogge: None declared